WII FIT IN THE TRAINING OF THE FUNCTIONAL EQUILIBRIUM OF ADULTS WITH INTELLECTUAL DEFICIT - Oliva, Daniela Regina Sposito Dias; Lima, Edina Alves de; Portella, Marilene Rodrigues; Benelli, Denise Almeida; Innig, Franciele Almeida (Revista ORL, 2018)
Introduction: Postural control involves balance, neuromuscular coordination and adaptation, whose automatic responses are adjusted to meet the needs of interaction between peripheral postural systems: vestibular, visual and somatosensory and central control. People with intellectual deficits may exhibit declining functions of balance, as well as having their functional capacities diminished in the absence of full control of posture (SCHIAVINATO et al, 2010). Physical therapy aimed at the prevention of falls can act in the scope of prevention as in recovery, restoring previously lost motor functions for the best adaptation to the environment. As a way of increasing balance and preventing falls, Wii rehabilitation consists of promoting the representation of the body in graphic images, in which there is interaction between the individual and the machine, being possible the association of behaviors and reactions to virtual objects, which promotes feedback for immediate bodily adjustments. In addition, it encourages the active participation of the player, motivator for learning and facilitator of the perceptual and motor skills and abilities of the same. Objective: To verify the static, dynamic and risk of falls in adults with moderate intellectual disabilities who attend the Association of Parents and students of exceptional - APAE, Concordia-SC-Brazil. Also verify the influence of virtual reality as a resource of balance training, before and after two months of intervention. Methods: Descriptive quantitative research, carried out with five students with moderate intellectual disabilities, aged between 32 and 55 years. The intervention took place using Nintendo Wii, with games Wii Fit Plus and Wii Sports. They were assessed by physical and functional tests, and they assessed their abilities / abilities for balance and risk of falls. Used the Berg balance scale and Timed Up and Go (TUG) test. The intervention consisted of 40 minute therapies performed once a week for two months. Results: In the Berg scale the items: Standing with one foot in front of the other and Standing with one foot, presented lower scores, which require static balance in also and unipodal support, corroborating with other studies, such as Taguchi and Santos (2007), who verified the tendency to fall in 130 elderly, and in Berg the task in unipodal support was the most compromised; and Wang et al (2006), who verified the same difficulties in 268 elderly people. It is observed in these participants with intellectual disability, low risk of falls, related to the time covered. In the descriptive statistical analysis comparing BERG scores, there was no improvement (51 points in 03 of the participants, 52 in 01 of them, and 54 points in 01 participant). In the TUG test they decreased from an average of 13 to 12 seconds, that is, without significant improvement. Conclusion: On the results obtained, intervention over two months, more than once a week is suggested, with application of the Wii associated with therapeutic resources as an example, platform on the balance pad, and use of other games that stimulate the posture in unipodal support and also with the yoga game for participants with these characteristics.